2015
DOI: 10.1089/gtmb.2015.0051
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Consumer Genetic Testing: A Systematic Review of European Guidelines, Recommendations, and Position Statements

Abstract: Professional societies and associations are currently more suggestive of potential disadvantages of DTC GT, recommending improved genetic literacy of both populations and health professionals, and implementation research on the genetic tests to integrate public health genomics into healthcare systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…This fragmentation has also been described in a recent systematic review of European guidelines, recommendations and position statements. 12 Our assessment was based on a simple, actionable, yes/no checklist. We did not specifically examine the fitness-for-purpose of contract language relevant to the HGC principles and this would merit further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fragmentation has also been described in a recent systematic review of European guidelines, recommendations and position statements. 12 Our assessment was based on a simple, actionable, yes/no checklist. We did not specifically examine the fitness-for-purpose of contract language relevant to the HGC principles and this would merit further study.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been observed that numerous European policy reports on DTC-GT have been written but few have been implemented. 12 We recommend new efforts to agree minimum standards of transparency and quality, with appropriate mechanisms of review and certification of DTC-GT providers to increase the accountability of companies active in the DTC-GT market. Providing an independent trusted quality mark would benefit both consumers and health-care professionals dealing with questions from patients who have purchased or are thinking of purchasing DTC-GT services.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…DTC testing has been criticized by both professional and public bodies (Rafiq et al 2015; Skirton et al 2012). Concerns have been expressed about the pre- and post-test information and counseling; medical supervision; consumer’s privacy and confidentiality; the test’s quality; and the possible impact on regular healthcare (Borry et al 2011; Skirton et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of genetic information for health purposes such as tailored dietary recommendations has been around for more than a decade (Rafiq, Ianuale, Ricciardi, & Boccia, 2015;Stover, 2004), this dissertation shows that the extent to which individuals know and understand the relevance of genetic information for the formation of meaningful dietary recommendation is limited. In addition, our findings show that personalised nutrition advice that is based on genotypic information significantly increases risk perceptions without enhancing perceptions of benefit.…”
Section: Practical Implicationsmentioning
confidence: 99%